EDUCAÇÃO MUSICAL NA ESCOLA: VALORIZAR O HUMANO EM CADA UM DE NÓS - Soares, Olavo Pereira; Cerveira, Rosimeire Bragança; Mello, Suely Amaral [UNESP] (Centro de Estudos Educação e Sociedade, 2019)
The article analyzes research data developed with students attended by a full-time public-school program - 90% of them in situations of social vulnerability. The data was collected by the music teacher who carried out an academic research on the subject. This work’s goal is to demonstrate that music education in school can bring a humanizing perspective, when educating in music means to enable the learning of music as a historical, social and cultural phenomenon, that can be understood and produced by all human beings.

O presente artigo analisou dados de pesquisa desenvolvida com alunos atendidos por um programa de escola pública em tempo integral, 90% desses em situação de vulnerabilidade social. Os dados foram coletados pela professora de música que realizava pesquisa acadêmica sobre a temática. O objetivo foi demonstrar que a educação musical na escola pode adotar uma perspectiva humanizadora, quando educar em música significa possibilitar a aprendizagem da música como fenômeno histórico, social e cultural, passível de ser compreendida e produzida por todos os seres humanos.
Music education in school: valuing the human in each of us
Keywords: Musical education; Humanization; Cultural-historical approach; Educação musical; Humanização; Perspectiva histórico-cultural